Laser Resection of Lung Tissue: Heat Accumulation from Adjacent Laser Application and How to Cool It Down - Kirschbaum, Andreas; Rexin, Peter; Pehl, Anika; Bartsch, Detlef; Quint, Karl (The Thoracic and Cardiovascular Surgeon, 2014)
Background Heat accumulation might induce thermal damage of the surrounding lung tissue, especially when multiple lesions are resected in one session. The present study aimed to investigate whether heat accumulates in the immediate vicinity of the resection surface and leads to thermal damage of the lung parenchyma, and what is the most effective cooling strategy in this situation.Materials and Methods In normothermic perfused paracardial swine lobes (n = 6), four punctiform laser lesions forming a square were created. Each lesion was lasered at a power of 100 W for 5 seconds. Two test conditions with square sides of either 1.0 or 0.5 cm were compared. Temperatures were recorded immediately after completing the laser procedure in the square center and in the corners using a thermal camera and continued during the cooling process at 10-second intervals until normothermia (37°C). We examined two cooling methods: rinsing with ice-cold (4°C) Ringer solution during the laser procedure (group B, n = 6) or submerging the lung in ice-cold water for 5 seconds immediately after laser application (group C, n = 6). In the control group A (n = 6), there was no cooling.Results In the 0.5 cm squares, mean temperature in the center immediately after laser application was 103.17 ± 8.56°C, significantly higher than in the corners (76.39 ± 2.87°C, p < 0.05). Normothermia in the quadrant corners was reached after 81 ± 14 and after 108 ± 29 seconds in the centers. Tissue in the square center revealed histological signs of thermic cell damage. In the 1.0 cm squares, mean temperature in the center was 64 ± 5°C, and in the corners was 77 ± 3.1°C (p < 0.05). Normothermia was regained after 93 ± 22 seconds in the center and 120 ± 21 seconds in the corners. Histological examination in the 1.0-quadrant centers revealed no signs of thermic cell damage. Submerging the lobe into ice-cold water lowered the temperature rapidly to under 40°C, and normothermia was regained after 75 ± 1.3 seconds.Conclusion Laser application to the lung parenchyma causes considerable heat accumulation in closely related lesions. To prevent such cell damage, a distance of at least 1.0 cm between laser targets should be maintained. If no topical cooling method applied, sufficient time for spontaneous tissue cooling before additional laser application should be provided. The most effective cooling strategy against heat accumulation is submerging in ice-cold water for at least 5 seconds.
Keywords: experimental; metastases/metastasectomy; surgical equipment